2009
DOI: 10.2174/138161209789909692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Polyunsaturated Fatty Acids on Mitochondria

Abstract: Type and quantity of ingested dietary fat contribute to the onset and progression of chronic diseases such as diabetes, obesity or arteriosclerosis. Attention is increasingly focussing on effective therapies for these diseases as well as functional foods that impede the development of insulin resistance and obesity. Studies provided evidence showing polyunsaturated fatty acids of the omega-3 and the omega-6 families play beneficial roles in prevention and treatment of diseases as diverse as Alzheimer's disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 155 publications
(261 reference statements)
2
33
0
2
Order By: Relevance
“…Altered CL unsaturation and oxidative susceptibility of the mitochondrial membrane modulate the binding and activities of associated proteins, mainly of the pro- and antiapoptotic proteins of the Bcl-2 family. Changes of mitochondrial transition pore opening, decreased mitochondrial membrane potential, CL oxidation, and the release of proapoptotic cytochrome c and Apaf1 molecules are necessary for the execution of the intrinsic mitochondrial apoptotic pathway [140, 141]. Thus, in colonocytes and colon cancer cells, DHA alone or in combination with other agents can induce apoptosis by promotion of the mitochondrial apoptotic pathway as reported by us and others [131, 133, 142].…”
Section: Interactive Effects Of Dietary Fatty Acids With Tnf Familmentioning
confidence: 83%
“…Altered CL unsaturation and oxidative susceptibility of the mitochondrial membrane modulate the binding and activities of associated proteins, mainly of the pro- and antiapoptotic proteins of the Bcl-2 family. Changes of mitochondrial transition pore opening, decreased mitochondrial membrane potential, CL oxidation, and the release of proapoptotic cytochrome c and Apaf1 molecules are necessary for the execution of the intrinsic mitochondrial apoptotic pathway [140, 141]. Thus, in colonocytes and colon cancer cells, DHA alone or in combination with other agents can induce apoptosis by promotion of the mitochondrial apoptotic pathway as reported by us and others [131, 133, 142].…”
Section: Interactive Effects Of Dietary Fatty Acids With Tnf Familmentioning
confidence: 83%
“…The level of practice (trained men versus sedentary) and the supplement-related differences between studies could explain the difference in oxidative responses at baseline after n-3 LCPUFA supplementation (McAnulty et al 2010). Moreover, although n-3 LCPUFAs have beneficial effects in delaying the development of various diseases (Rohrbach 2009), it has been shown that their ingestion can result in increased lipid peroxidation (Guichardant et al 2006). These authors reported that the peroxidation of n-3 LCUFAs, which produces 4-hydroxy-2E-hexenal (4-HHE), is higher than the peroxidation of n-6 LCUFAs, although n-3 FAs are much lower than those of n-6 in most tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that the beneficial effect of n-3 PUFA supplementation on oxidative stress is controversial. Rohrbach (2009) reported that PUFAs can modulate ROS generation, but due to the complexity of their actions and the mechanisms involved, their effects are difficult to predict. McAnulty et al (2010) suggested that consumption of n-3 LCPUFAs does not increase peroxidation until a state of high oxidative stress is initiated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations